Analysis Of Factors Related To The Incidence Of Anemia In Pregnant Women In The Working Area Of The Community Health Center - Dewi Hastuty; Rosida Rosida (International Journal of Health Sciences, 2026)
Background : Anemia during pregnancy remains a significant public health problem worldwide and contributes to maternal and neonatal morbidity and mortality . Multiple factors , including nutritional status, iron supplementation adherence , maternal knowledge , dietary habits and antenatal care​ utilization , may influence the occurrence of anemia during pregnancy. Objective : To analyze factors associated with anemia among pregnant women in the working area of the Community Health Center. Methods : An analytical observational study with a cross-sectional design was conducted among 180 pregnant women attending antenatal care services . Samples were selected using proportional random sampling. Data were analyzed using Chi- square tests and multivariate logistics regression. Results : The prevalence of anemia was 34.4% . Nutritional status, adherence to iron supplementation , maternal knowledge , dietary habits , and antenatal care visits were significant associated with anemia (p < 0.05). Multivariate analysis identified adherence to iron supplementation as the strongest associated factor (AOR = 4.12; 95% CI: 2.01–8.43). Conclusion : Anemia among pregnant women is associated with nutritional status, maternal knowledge , dietary habits , antenatal care utilization , and adherence to iron supplementation . Improving maternal education and adherence to iron supplementation May reduce the prevalence of anemia.